2016
DOI: 10.1136/archdischild-2016-312055
|View full text |Cite
|
Sign up to set email alerts
|

The changing UK paediatric consultant workforce: report from the Royal College of Paediatrics and Child Health

Abstract: Objectives: To determine if there had been changes in the size of the UK paediatric workforce and working patterns between 1999 and 2013.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…One reason for this inequity may be the existence of a training capacity gap, with fewer avenues to train paediatricians or fewer opportunities for employment in areas with an already low workforce. Some high-income countries have already undertaken more detailed analysis of their paediatric workforce and used this to inform investment and education policy 14 20–24…”
Section: Discussionmentioning
confidence: 99%
“…One reason for this inequity may be the existence of a training capacity gap, with fewer avenues to train paediatricians or fewer opportunities for employment in areas with an already low workforce. Some high-income countries have already undertaken more detailed analysis of their paediatric workforce and used this to inform investment and education policy 14 20–24…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the workforce for academic medicine as a whole was at best stable compared with the year-on-year growth of National Health Service (NHS) staff. In child health, we have also seen growth in NHS staff, but sadly have highlighted a marked decline in the academic workforce 7. The MSC further emphasised the substantial impact of NIHR funding in England, and that work is actively being pursued to support early-stage clinical academics.…”
Section: Discussionmentioning
confidence: 99%
“…Given the variability of undergraduate radiology education delivered in universities across the UK [13] and Europe [14], the fact that most junior doctors do not feel confident interpreting paediatric radiographs [3] with added workforce issues relating to both paediatric radiology [15], paediatric emergency services [16] and paediatric medicine [17], it is likely that having some exposure to paediatric radiology at an undergraduate level may prove beneficial in later medical practice [18]. As puzzles within an escape room are problem-based and require communication and team-working skillsconsidered intrinsic parts of the way in which adults learn [19], we hypothesised that this teaching method would lend itself well to an undergraduate paediatric radiology tutorial.…”
Section: Introductionmentioning
confidence: 99%